Safety criteria against blast vibrations for structures in green and fully cured concrete - Keshav, G.R. Tripathy; Gupta, I.D. (Journal of Structural Engineering, 2024)
Rock excavation by blasting may be involved near structures under construction with green concrete in many civil engineering activities. If not safeguarded properly, the weakening of green concrete may affect the performance of a structure of interest at later stage. Similar to that for fully cured concrete, the safety criteria to ensure the safety of green concrete of different ages are also defined in terms of peak particle velocity. Most of the existing safety criteria for green concrete are based mainly on the development of tensile strength with age. They are thus seen to differ widely, because the strength values are seen to be scattered widely due to quite complicated dependence on the material properties and the curing condition. This paper reviews the various published safety criteria for green concrete and proposes suitable guidelines to obtain site-specific safety criteria based on a more stable characteristic, viz. dynamic strain capacity. The only information required to arrive at the site-specific criteria for a given age of concrete is its compressional wave velocity, the average value of which can be obtained with very good confidence. The safety criteria thus obtained are shown to be compatible with the safe limits obtained by direct observations of damage on fully cured concrete blocks subjected to different level of blast vibrations. Using a large database collected from several project sites in India, generalized and unified safety criteria of wider applicability are proposed for green as well as fully cured concrete.